Mutualism and the Law of Comparative Advantage - Wagner, Gerhard (Zeitschrift für Theoretische Soziologie, 2020)
This paper contributes to the clarification of the emergence of mutualistic relations by means of the Law of Comparative Advantage. Developed in economics and applied metaphorically in biology, this law expresses a typical course of behaviour such as that described in the Second Law of Thermodynamics. It can be conceived as a minutis rectis law and in analogy to the Second Law of Thermodynamics linked to sociology via Max Weber’s position.